Pharmacological interventions targeting β-adrenoceptors in colorectal cancer: an evolving paradigm - Aya Ghosn (22997230) (2025)
Colorectal cancer (CRC) is a significant global health challenge, ranking as the third most common cancer and the second leading cause of cancer-related deaths worldwide. Its development is influenced by several risk factors, including smoking, diets rich in red meat, and the effects of stress-related hormones such as epinephrine and norepinephrine. These hormones act through β-adrenergic receptors (β-ARs), which are present on CRC cells and are associated with cancer-promoting processes such as increased cell growth, invasion, blood vessel formation, and accelerated disease progression. Notably, β-ARs blockers have shown potential in slowing CRC progression, pointing to a promising therapeutic strategy. This review explores the main signaling pathways through which β-ARs contribute to cancer development and how various risk factors may influence these mechanisms. We also provide an overview of current preclinical and clinical studies on β-AR blockers in CRC, identify existing gaps in knowledge, and propose directions for future research to optimize therapeutic outcomes. Other Information Published in: Inflammopharmacology License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s10787-025-01925-5